An unusual interventricular septal bounce in a patient with dermatomyositis: a case report. Issue 2 (30th April 2019) - Parato, Vito Maurizio; Corradini, Davide; Di Matteo, Andrea; Scarano, Michele
Abstract: Background: In literature it has been reported in 1998, for the first time, a case of a 54-year-old man who developed constrictive pericarditis (CP) 12 years after diagnosis of dermatomyositis (DM). To our knowledge, this may be the only case reported. Case summary: A 16-year-old man presented to our institution because of symptoms posing a suspicion for an inflammatory disease; after physical examination, lab tests, and other investigations (electromyography, magnetic resonance, and muscular biopsy) was diagnosed as having DM. Patient also showed hepatomegaly and congested jugular veins: after clinical and imaging investigations (transthoracic echocardiography and transoesophageal echocardiography) he was diagnosed as having a CP. Patient underwent pericardial resection and the final outcome consisted of a completely regression of the symptoms. Discussion: Cardiac involvement in patients with DM ranges between 6% and 75%, and it can be clinically manifest or, far more frequently, sub-clinic. Pericardial involvement as a complication of DM is widely reported in the literature, but in almost all cases as acute pericarditis, effusive pericarditis or cardiac tamponade and almost never as a CP.